2008 International Conference on Computer and Communication Engineering 2008
DOI: 10.1109/iccce.2008.4580829
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent dynamic traffic light sequence using RFID

Abstract: The proposed RFID

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Plot designed in sub-image (b) of Fig. 4 compares their amounts through different frames • False detection rate (Al-Khateeb et al, 2008) is the third quantitative factor used in this research. Actually, it is equal to the number of pixels which the difference between their values and the value of corresponding pixel in the adapted background calculated with the less combination rate is more than a user predefined threshold (γ).…”
Section: Resultsmentioning
confidence: 99%
“…Plot designed in sub-image (b) of Fig. 4 compares their amounts through different frames • False detection rate (Al-Khateeb et al, 2008) is the third quantitative factor used in this research. Actually, it is equal to the number of pixels which the difference between their values and the value of corresponding pixel in the adapted background calculated with the less combination rate is more than a user predefined threshold (γ).…”
Section: Resultsmentioning
confidence: 99%
“…A lot of research has been done on TLCs which use different technologies e.g. [4,7,8,10,13] just to mention a few. Recently, two TLCs have been proposed based on WSNs too [15,9].…”
Section: Traffic Light Controllersmentioning
confidence: 99%
“…Niittymaki in [12] presented a field test of a simple two-phase fuzzy signal controller. The results showed that the fuzzy logic controller performed better than vehicle-actuated control in terms of delay, percentage stops and savings in fuel and emissions.…”
Section: Related Workmentioning
confidence: 99%